Management of feline carpal injuries: What are the options and when is arthrodesis indicated?. Issue 9 (September 2019) - Basa, Rachel M; Johnson, Kenneth A
Practical relevance: Feline carpal injuries are usually caused by falls from a height that result in hyperextension injury or antebrachiocarpal luxation or subluxation. Isolated ligamentous damage or fracture of the carpus is unusual; it is more common to have a combination of both in the cat. These injuries can be debilitating since cats climb and jump from great heights, and have a greater range of antebrachial pronation and supination than dogs. Anatomy: There are differences in the anatomy of the feline and canine carpus. In particular, cats only have a single short radial collateral ligament, also known as the medial collateral ligament. This means that, in the cat, antebrachiocarpal subluxation is possible with rupture of the dorsal joint capsule and short radial collateral ligament alone. Clinical challenges: Many feline carpal injuries can be treated without performing pancarpal arthrodesis. However, determining which ligaments and joint levels are affected requires careful examination and often stress radiography. When pancarpal arthrodesis is performed in the cat, it has been reported to reduce the height of jumping and to increase reluctance to climb. This is speculated to be due to reduced pronation and supination movement of the carpus. Evidence base: The current evidence base for management of feline carpal injuries is grade III or IV, with most of the studies being retrospective case series involving cadaveric dissection or direct extrapolation from published information about the dog. There are few guidelines regarding the optimal treatment options for carpal injuries in the cat.